Change in abdominal obesity and risk of coronary calcification. Issue 3 (4th February 2011) - Sabour, Siamak; Grobbee, Diederick E; Prokop, Mathias; van der Schouw, Yvonne T; Bots, Michiel L
Abstract : Background: A prospective follow-up study was conducted to examine the relationship between 9 year change in abdominal obesity and risk of coronary artery calcification (CAC). Methods: Data on coronary risk factors for 573 postmenopausal women were collected at baseline (1993–1997) and follow-up (2002–2004). At follow-up, the women underwent a multidetector CT to assess coronary calcium using the Agatston score. Markers of abdominal obesity were waist and hip circumference, waist-to-hip ratio (WHR) and body mass index. Results: Compared to subjects whose waist circumference remained below the median at both occasions, those with a waist above the median had a 1.5-fold (95% CI 1.0 to 2.3) increased risk of CAC. Women whose waist rose over the 9 year period had a 2.2-fold (95% CI 1.1 to 4.2) increased risk of CAC, whereas women whose WHR became lower had a non-significant 1.5-fold increased risk of CAC (95% CI 0.7 to 3.0). In contrast, change in body mass index or hip circumference was not related to risk of CAC. Conclusion: This study supports the existing evidence that persistent abdominal obesity, as well as an increase in abdominal fat, relates to an increased risk of coronary atherosclerosis.